1998
DOI: 10.1115/1.2798022
|View full text |Cite
|
Sign up to set email alerts
|

The Penn State Safety Floor: Part I—Design Parameters Associated With Walking Deflections

Abstract: A new flooring system has been developed to reduce peak impact forces to the hips when humans fall. The new safety floor is designed to remain relatively rigid under normal walking conditions, but to deform elastically when impacted during a fall. Design objectives included minimizing peak force experienced by the femur during a fall-induced impact, while maintaining a maximum of 2 mm of floor deflection during walking. Finite Element Models (FEMs) were developed to capture the complex dynamics of impact respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Previous studies involving quiet stance and backwards perturbations in elderly individuals revealed clinically insignificant differences in postural sway between some safety floors and traditional floors [15,23]. In order to examine a more dynamic task scenario, the flat-foot stage of single-leg stance during a natural cadence gait-cycle was simulated in this study to contribute to existing literature on locomotor adaptations, footfall deflections and toe-floor clearance distances while walking on compliant surfaces [22,24,25]. In addition, this approach corresponds to recommendations that "future research into the role of floor compliance in balance in older adults should include studies of walking" [33].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies involving quiet stance and backwards perturbations in elderly individuals revealed clinically insignificant differences in postural sway between some safety floors and traditional floors [15,23]. In order to examine a more dynamic task scenario, the flat-foot stage of single-leg stance during a natural cadence gait-cycle was simulated in this study to contribute to existing literature on locomotor adaptations, footfall deflections and toe-floor clearance distances while walking on compliant surfaces [22,24,25]. In addition, this approach corresponds to recommendations that "future research into the role of floor compliance in balance in older adults should include studies of walking" [33].…”
Section: Introductionmentioning
confidence: 98%
“…Control of balance is dependent on the central nervous system continually integrating visual, vestibular, and somatic sensory information about the surrounding environment, orientation of body parts, and forces acting on the body [20]. Soft foam surfaces detrimentally affect somatic sensory inputs from proprioceptive muscle spindles and cutaneous receptors in the foot and ankle, leading to a delayed or misguided balance control response [21,22]. Thus, a crucial design element for effective safety floors is the ability to provide substantial force attenuation without allowing deflections that may impair balance control during gait and stance activities.…”
Section: Introductionmentioning
confidence: 99%
“…To develop new intervention strategies such as impact attenuating safety floors (Casalena et al, 1998;Laing et al, 2006), more data are needed on the dynamics of backward fall and injury locations for various fall configurations.…”
Section: Introductionmentioning
confidence: 99%
“…A study into the design of a safety floor stated that it must reduce peak impact forces in a fall and also remain relatively rigid under normal walking conditions with less than 2 mm deflection [16,17]. Under impact conditions from a fall, the floor would deform much more than 2 mm to absorb the greater kinetic energy.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials have limited damping properties when there are high impact energies involved as in a typical fall. There is an increasing amount of research into the impact properties of floor coverings [16,17,18]. The aim of this work is to describe a new technique for accurate simulation of typical impact conditions and a method for analysis of results.…”
Section: Introductionmentioning
confidence: 99%